BIOGRAFI MAYOR ZUHDI TAHUN 1933-2005 - Rita Oktavia; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: Biography is the story of a person’s life history sourdced from true stories written by others. Biography tells a proscess starting from thr childhood of the character including his family background ad environment. The other raise a biography about the life journey of a military figure who fougt in Indonesia’s independence from the invaders, namely the Major Zuhdi. As for the purpose of this study id 1) To find out the life history of Major Zuhdi, 2) To find out the story of the Major Zuhdi struggle in maintaining independence in the downstream Indragiri Hilir, 3) To find out the end of the struggle of Major Zuhdi. The method used is the historical method, qualitative descriptive method, and data collection techniques in the form of interviews, literature, andted in the documentation.. The results of this research can be concluded that Major Zuhdi is a military figure who fought in the defense of Indonesian independence, especially int the Indragiri Hilir area. In 1946 Major Zuhdi took part in the bettle of the of the Tanjung Kilang raid on Pulau Durai, and in 1947 in the Perigi Raja.Key Words: Biography, Major Zuhdi, Warrior,Independence